2021
DOI: 10.1007/s00170-021-07333-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and corrosion resistance properties of AA7075-T6 sub-zero formed sheets

Abstract: The poor formability of 7xxx series aluminium alloys represents the major limit to their actual use for automotive and aerospace applications. In the present study, the forming temperature effect on the mechanical, corrosion and anodization behaviours of the AA7075-T6 alloy is investigated. To this purpose, tensile tests at different temperatures, ranging from −100 to 300°C, were carried out at different rolling directions. A 6.6% increase of the ultimate tensile strength and a 28.6% increase of the uniform el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…The corrosion resistance of a FSWed joint in aluminum alloys 6082-T6/7075-T6 improves significantly compared to the BM. A more negative Ecorr and a higher Icorr density indicate a greater tendency for corrosion [43]. In this case, a notably higher negative Ecorr value of 1455.9 mV and a higher Icorr density of 174.3 μAcm -2 were observed at 40 mm/min and 2300 rpm, indicating lower corrosion resistance.…”
Section: Corrosion Behaviormentioning
confidence: 78%
“…The corrosion resistance of a FSWed joint in aluminum alloys 6082-T6/7075-T6 improves significantly compared to the BM. A more negative Ecorr and a higher Icorr density indicate a greater tendency for corrosion [43]. In this case, a notably higher negative Ecorr value of 1455.9 mV and a higher Icorr density of 174.3 μAcm -2 were observed at 40 mm/min and 2300 rpm, indicating lower corrosion resistance.…”
Section: Corrosion Behaviormentioning
confidence: 78%
“…The corrosion behavior of the material was generally dependent on the surface quality, grain size, and residual stresses because corrosion is a surface phenomenon. 41 According to Bertolini et al, 42 higher surface roughness led to a reduction in corrosion resistance due to the increment in the contact part between the corrosive medium and the surface. Additionally, Esteves et al 43 depicted that grain refinement and higher hardness were responsible for superior corrosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of a gradually decreasing corrosion rate indicates the passivation of the material due to the formation of a permanent protective layer, i.e., Al2O3, which plays a crucial role in the process of improving corrosion resistance [22][23][24][25][26]. The corrosion data revealed that the icorr value decreased for 3 wt.% and 9 wt.% TiC relative to the starting material.…”
Section: Microstructural Observations Of Worn Samplesmentioning
confidence: 99%